Letermovir for cytomegalovirus prophylaxis in high‐risk heart transplant recipients. Issue 12 (26th October 2022) - Golob, Stephanie; Batra, Jaya; DeFilippis, Ersilia M.; Uriel, Matan; Carey, Matt; Gaine, Maureen; Mabasa, Angelo; Fried, Justin; Raikelkar, Jayant; Restaino, Susan; Hi Lee, Sun; Latif, Farhana; et al.
Abstract: Letermovir is a novel agent for the prevention of cytomegalovirus (CMV) infection and disease that, unlike traditional CMV DNA polymerase inhibitors, does not carry the risk of myelosuppression. The purpose of this study was to evaluate the safety, efficacy, and clinical application of letermovir for CMV prophylaxis in heart transplant (HT) recipients. Between November 1, 2019, and October 1, 2021, at a single, tertiary care hospital, 17 HT recipients were initiated on letermovir due to leukopenia while on valganciclovir. Fifteen (88%) had high‐risk mismatch (CMV D+/R‐). Median time on letermovir was 5 months (interquartile range, 2–8 months.) At the end of the study period, nine of 17 patients (52.9%) were still on letermovir and four of the 17 (23.5%) had successfully completed the prophylaxis window on letermovir and been switched to the pre‐emptive strategy. One patient developed clinically significant CMV viremia in the setting of being unable to obtain medication due to insurance barriers but was later successfully restarted on letermovir. One patient was unable to tolerate letermovir due to symptoms of headache and myalgias. Two patients developed low‐level non‐clinically significant CMV viremia and were switched back to valacyclovir. All patients had tacrolimus dosages reduced at time of letermovir initiation to minimize the risk of supratherapeutic tacrolimus concentration. One patient required hospitalization due to symptomatic tacrolimus toxicity. For HT recipients who cannot tolerate valganciclovir, letermovir presents an alternative for CMV prophylaxis. Close monitoring for breakthrough CMV and calcineurin inhibitor levels is necessary. Larger studies are required to further delineate its use and help provide further evidence of its safety and efficacy.